Знаю
Объяснение:
1. На фото
2. На фото
3. На фото
4. На фото
5. На фото
6. На фото
7. 0 {
(x+1)
2
+(y−1)
2
=(x+4)
2
+(y+2)
2
−18
(x−y)(x+y)−x(x+10)=y(5−y)+15
\left \{ {{x^2-y^2 -x^2- 10x = 5y - y^2 + 15} \atop {x^{2} +2x+1+y^2-2y+1=x^2+8x+16+y^2+4y+4-18}} \right.{
x
2
+2x+1+y
2
−2y+1=x
2
+8x+16+y
2
+4y+4−18
x
2
−y
2
−x
2
−10x=5y−y
2
+15
\left \{ {{-y^2- 10x - 5y + y^2 - 15=0} \atop {x^{2} +2x+y^2-2y+2=x^2+8x+y^2+4y+2}} \right.{
x
2
+2x+y
2
−2y+2=x
2
+8x+y
2
+4y+2
−y
2
−10x−5y+y
2
−15=0
\left \{ {{- 10x - 5y- 15=0} \atop {x^{2} +2x+y^2-2y+2-x^2-8x-y^2-4y-2=0}} \right.{
x
2
+2x+y
2
−2y+2−x
2
−8x−y
2
−4y−2=0
−10x−5y−15=0
\left \{ {{- 10x - 5y- 15=0}|:(-5) \atop {-6x-6y=0}} \right.{
−6x−6y=0
−10x−5y−15=0∣:(−5)
\left \{ {{2x +y+3=0} \atop {-6x-6y=0}|:(-6)} \right.{
−6x−6y=0∣:(−6)
2x+y+3=0
\left \{ {{2x +y+3=0} \atop {x+y=0}} \right.{
x+y=0
2x+y+3=0
x+y=0x+y=0 => x=-yx=−y
2*(-y) +y+3=02∗(−y)+y+3=0
-2y +y=-3−2y+y=−3
-y=-3−y=−3
y=-3:(-1)y=−3:(−1)
y=3y=3
x=-yx=−y => x=-3x=−3
x+y=-3+3=0x+y=−3+3=0 сума
Вiдповiдь: 0
Объяснение:
1)
a) x² - 6x + 5 = 0;
D = 16;
X1 = 5;
X2 = 1;
ответ: 5, 1
б) x² - 5x = 0;
x (x - 5) = 0;
X = 0 или x = 5;
ответ: 0, 5
в) 6x + x²- 7 = 0
x² + 6x - 7 = 0
D=6²-4*1*7=36-28=√8=2√2
x1 = -2√2
x2 = -4√2
ответ: -2√2, -4√2
г) 3x² - 48 = 0
3 (x² - 16) = 0
(x - 4) (x + 4) = 0
x1 = 4
x2 = -4
ответ: 4, -4
2)
S = x (x - 6) = 40
x² - 6x - 40=0
D = 36 + 160 = 196 = 14²
x₁ = (6 + 14) / 2 = 10
x₂ = (6 - 14) / 2 = -4
Длина = 10
Ширина = 10 - 6 = 4
3)
х² + рх - 18 = 0
81 - 9p - 18 = 0
-9p = -63
p = 7
x² + 7x - 18 = 0
x₁ = -9 x₂ = 2
4)
х1 + х2 = -b;
x1 * x2 = c
9 - 4 = 5 b = -5
9 * (-4) = 36 c = -36
х² - 5х - 36 = 0
I hope this helps you